2014
DOI: 10.1002/bmc.3240
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of cyclophosphamide administration alone and combination with vitamin B6 in rats

Abstract: A fast and sensitive high performance liquid chromatography coupled with mass spectrometry (LC-MS) method was developed and validated for the determination of cyclophosphamide in rat plasma with and without the combination of vitamin B6. After addition of digoxin used as the internal standard (IS), plasma samples were extracted by protein precipitation with acetonitrile (1:1, v/v), and the analytes were separated by a Kromasil C18 column (150 × 4.6 mm, 5 µm) with a mobile phase of acetonitrile-0.1% formic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…showed pairing targeted therapeutics with subtherapeutic doses of broad acting “network brake” drugs extended therapeutic utility while reducing whole body toxicity. Since its first discovery, CY has been used as an anticancer drug for more than 40 years in clinical practice, and remains to be a main chemotherapy drug for multiple cancers . Despite its significant therapeutic effects, the serious toxicity and side effects of CY have remained a major hindrance on the prognosis and quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…showed pairing targeted therapeutics with subtherapeutic doses of broad acting “network brake” drugs extended therapeutic utility while reducing whole body toxicity. Since its first discovery, CY has been used as an anticancer drug for more than 40 years in clinical practice, and remains to be a main chemotherapy drug for multiple cancers . Despite its significant therapeutic effects, the serious toxicity and side effects of CY have remained a major hindrance on the prognosis and quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide (CP) is widely used in the treatment of numerous malignant diseases and in the treatment of colon cancer. CP stimulates apoptosis as the result of interaction with cellular macromolecules such as: proteins, membrane lipids, RNA and DNA (2). In animal model studies performed during the last decade, CP, which has been suggested as a salvage therapy in low doses to prevent tumour angiogenesis in end-stage cancer patients, has also been shown to have an immunomodulatory effect (3).…”
Section: Introductionmentioning
confidence: 99%